Autoimmune hypophysitis - Ileana-Dumbrava, Ecaterina; Subbiah, Vivek (The lancet oncology, 2018)
A 82-year-old male patient with metastatic lung adenocarcinoma presented to the outpatient clinic at the University of Texas MD Anderson Cancer Center (Houston, TX, USA) in April, 2015 with worsening fatigue, headache, dizziness, blurry vision, and nausea. Immune checkpoint inhibitors such as anti-CTLA-4, anti-PD-1, or anti-PD-L1 antibodies are US FDA and European Medicines Agency-approved treatments for several tumour types, including non-small-cell lung cancer, and are emerging as a standard of care.